Self-awareness and introspection in Narcissistic Personality Disorder (NPD) - Sam Vaknin (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
With severe emotional deficits, the narcissist may be self-aware and knowledgeable about Narcissistic Personality Disorder, but these do not lead to healing, merely to behaviour modification. Narcissists balance a sadistic superego and a demanding and fantastic False Self. Narcissists describe themselves as machines or automata.  When they do gain self-awareness and engage in soul-searching it is in order to enhance their skills at attracting and maintaining their sources of narcissistic supply.